Pengaruh Beban Kerja terhadap Turnover Intention pada Karyawan Panen dan Perawatan di Perusahaan Perkebunan Kelapa Sawit - Sodikin, Muhammad; Suswatiningsih, Tri Endar; Kurniawati, Fitri (AGRIFITIA : Journal of Agribusiness Plantation, 2024)
Employees are an important part of palm oil plantation companies. Employee workload needs to be considered so that they are comfortable when working.This research was carried out at PT Karya Makmur Bahagia which operates in the field of oil palm plantations and Crude Palm Oil (CPO) producers located in the Mentaya Region, Central Kalimantan. This research aims to determine the workload received by harvest and maintenance employees and determine the effect of workload on turnover intention among harvest and maintenance employees. This type of research is quantitative descriptive. The sample used in this research was 15 harvest employees and 15 maintenance employees using incidental sampling techniques. Data were analyzed using regression analysis. The research results showed that 47% of harvest employees had a moderate workload, and 47% of maintenance employees had a light workload. Workload has a positive effect on employee turnover intentions